Juridical Analysis of the Criminal Act of Distributing Trihexyphenidyl (Case Study: Decision Number 24/Pid.Sus/2024/PN Smn and Decision Number 288/Pid.Sus/2024/PN Yyk) - Maharani, Natasya; Retno Mumpuni, Niken Wahyuning (LEGAL BRIEF, 2025)
Trihexyphenidyl is a controlled drug prone to misuse, and its distribution without marketing authorization poses a serious threat to public health, particularly in the Special Region of Yogyakarta. This phenomenon frequently involves adolescents and presents significant challenges to law enforcement. This study aims to analyze the legal provisions, law enforcement practices, and sentencing disparities concerning offenders involved in the unauthorized distribution of Trihexyphenidyl, based on Decision Number 24/Pid.Sus/2024/PN Smn and Decision Number 288/Pid.Sus/2024/PN Yyk. The research employs a normative legal method through literature review and statutory analysis, complemented by an empirical approach involving interviews with law enforcement officials and the National Agency of Drug and Food Control (BPOM), as well as case studies of the two court decisions. The analysis is conducted qualitatively and descriptively. Both decisions affirm that unauthorized distribution constitutes a formal offense; however, sentencing disparities are evident, influenced by factors such as the offender’s role, the quantity of evidence, and mitigating circumstances. The primary challenges include proving mens rea, weak regulatory oversight, and the prevalence of online distribution. Law enforcement has recognized the unauthorized distribution of Trihexyphenidyl as a serious crime; nonetheless, consistency in sentencing and the strengthening of local regulations are required to close legal loopholes and enhance deterrence